Chemoradiotherapy in octogenarians as primary treatment for muscle-invasive bladder cancer - McPherson, Victor A.; Rodrigues, George; Bauman, Glenn; Winquist, Eric; Chin, Joseph; Izawa, Jonathan; Potvin, Kylea; Ernst, Scott; Venkatesan, Varagur; Sexton, Tracy; et al. (Canadian Urological Association Journal, 2017)
Introduction: While radical cystectomy is the gold standard for muscle-invasive bladder cancer (MIBC), in octogenarians cystectomy results in a higher perioperative mortality rate (6.8‒11.1%) than in younger patients (2.2%). Trimodality therapy is a bladdersparing regimen composed of transurethral resection of bladder tumour (TURBT) and chemoradiotherapy, with intent for salvage cystectomy, and has a 62.5‒90% initial complete response rate. In this study, we evaluate TURBT and chemoradiotherapy without salvage cystectomy in medically inoperable octogenarian patients. Methods: We identified a retrospective cohort of patients aged 80‒89 years with invasive urothelial carcinoma who received combination chemoradiotherapy between 2008 and June 2014. Outcomes were evaluated by Kaplan-Meier (KM) and Cox regression. Results: In 40 patients, the mean age was 84.5 years (interquartile range [IQR] 83‒86). Seventeen patients received hypofractionated, low-dose radiotherapy (LD) (37.5‒40 Gy), while 23 received conventionally fractionated radiotherapy (high-dose [HD]) (50‒65 Gy). Mean overall survival (OS) was 20.7 months (IQR 12.75‒23.25), while mean recurrence-free survival (RFS) was 13.75 months (IQR 3.75‒16.5). Patients receiving HD radiotherapy showed improved OS and local RFS (LRFS) without significant differences in Grade 3‒4 toxicities. Univariate Cox regression identified hydronephrosis as a predictor of worse OS and local recurrence and HD radiotherapy as a predictor of improved OS and local recurrence rates. Multivariate Cox regression identified hydronephrosis to be a significant predictor of LRFS. Conclusions: Primary chemoradiotherapy for inoperable patients with MIBC resulted in a three-year OS of 54.9% (comparable to cystectomy) and three-year RFS of 42.3%. Superior outcomes were associated with more aggressive chemoradiotherapy treatment. The results of the local control subanalyses in this study are hypothesisgenerating due to the limited patient numbers in the cohort.